-4a-4=7/4a-3

Simple and best practice solution for -4a-4=7/4a-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4a-4=7/4a-3 equation:



-4a-4=7/4a-3
We move all terms to the left:
-4a-4-(7/4a-3)=0
Domain of the equation: 4a-3)!=0
a∈R
We get rid of parentheses
-4a-7/4a+3-4=0
We multiply all the terms by the denominator
-4a*4a+3*4a-4*4a-7=0
Wy multiply elements
-16a^2+12a-16a-7=0
We add all the numbers together, and all the variables
-16a^2-4a-7=0
a = -16; b = -4; c = -7;
Δ = b2-4ac
Δ = -42-4·(-16)·(-7)
Δ = -432
Delta is less than zero, so there is no solution for the equation

See similar equations:

| 63=9(t-85) | | m/6+31=33 | | x=x5+78 | | 6+7=s | | 11=8n-15 | | y-36/4=10 | | 6+7=g | | 70=7(r+1) | | 8+7=k | | -74=-6c+-8 | | 2x^2+9x-5=) | | X=10x-7 | | 2u—2=26 | | 147÷n=21 | | 132/p=-12 | | -21.95=-3.6m-1.07 | | X=5x+78 | | w/3+10=18 | | 12=j+6 | | 3x+4=2x=27 | | 123/x=-12 | | 12=j6 | | 16=20-2u | | H=5+75t-16t2 | | 5x-61+64=180 | | -24=-4(-2k-3) | | -x=2=x-14 | | 7e−4=38 | | 18h+13h=31h | | 9x-6x+10=43 | | -9+3x=-8,1 | | -3(3x+1)=26 |

Equations solver categories